JURIDICAL REVIEW OF WASTE MANAGEMENT BY THE VILLAGE GOVERNMENT BASED ON THE CIREBON REGENCY REGULATION - Safina Ni'mah Azzahra; Deni Yusup Permana (Fakultas Hukum Universitas Swadaya Gunung Jati, 2026)
This study aims to analyze the implementation of the village government's obligations in waste management under Cirebon Regency Regional Regulation Number 5 of 2022, particularly Article 8, as well as the juridical implications of the unfulfilled facilities at the TPS in Ki Warga Gegesik Kidul Village. The method used is normative juridical with secondary (supportive) data. The results of the study show that the implementation of the village government's obligations has not been optimal, characterized by limited facilities and infrastructure as well as the accumulation of waste. Juridically, this indicates that legal obligations have not been fulfilled. In addition, the provisions of Article 8 that remain general indicate normative weaknesses that contribute to an lack of certainty and effectiveness of the law. Thus, clearer and operational arrangements and adequate facility support are needed so that waste management can run effectively and sustainably.